High‐throughput sequencing approach in analysis of microbial communities colonizing natural gas pipelines. Issue 8 (6th February 2019) - Staniszewska, Agnieszka; Kunicka‐Styczyńska, Alina; Otlewska, Anna; Gawor, Jan; Gromadka, Robert; Żuchniewicz, Karolina; Ziemiński, Krzysztof
Abstract: This study provides a deep modern insight into the phylogenetic diversity among bacterial consortia found in working and nonworking high‐methane natural gas pipelines located in Poland. The working pipeline was characterized by lower biodiversity (140–154 bacterial genera from 22 to 23 classes, depending on the source of the debris) in comparison to the off‐gas pipeline (169 bacterial genera from 23 classes). The sediment recovered from the working pipeline contained mostly DNA identified as belonging to the phylum Firmicutes (66.4%–45.9% operational taxonomic units [OTUs]), predominantly Bacillus (41.4%–31.1% OTUs) followed by Lysinibacillus (2.6%–1.5% OTUs) and Clostridium (2.4%–1.8% OTUs). In the nonworking pipeline, Proteobacteria (46.8% OTUs) and Cyanobacteria (27.8% OTUs) were dominant. Over 30% of the Proteobacteria sequences showed homologies to Gammaproteobacteria, with Pseudomonas (7.1%), Enhydrobacter (2.1%), Stenotrophomonas (0.5%), and Haempohilus (0.4%) among the others. Differences were noted in terms of the chemical compositions of deposits originating from the working and nonworking gas pipelines. The deposits from the nonworking gas pipeline contained iron, as well as carbon (42.58%), sulphur (15.27%), and oxygen (15.32%). This composition can be linked to both the quantity and type of the resident microorganisms. The presence of a considerable amount of silicon (17.42%), and of aluminum, potassium, calcium, and magnesium at detectable levels, may likewise affect the metabolic activity of the resident consortia in the working gas pipeline. All the analyzed sediments included both bacteria known for causing and intensifying corrosion (e.g., Pseudomonas, Desulfovibrio, Shewanella, Serratia ) and bacteria that can protect the surface of pipelines against deterioration (e.g., Bacillus ). Biocorrosion is not related to a single mechanism or one species of microorganism, but results from the multidirectional activity of multiple microbial communities. The analysis presented here of the state of the microbiome in a gas pipeline during the real gas transport is a particularly valuable element of this work. Abstract : The study provides a deep modern insight into the phylogenetic diversity of bacterial consortia in working and nonworking high‐methane natural gas pipelines localized in Poland. The working pipeline was characterized by lower biodiversity (140–154 bacterial genera from 22 to 23 classes depending on the debris localization) in comparison with the off‐gas pipeline (169 bacterial genera from 23 classes). DNA recovered from the working pipeline sediments represented mostly Firmicutes (45.9%–66.4% operational taxonomic units [OTUs]) with a dominance of Bacillus (31.1%–41.4% OTUs) followed by Lysinibacillus (1.5%–2.6% OTUs) and Clostridium (1.8%–2.4% OTUs). In the nonworking pipeline Proteobacteria (46.8% OTUs) and Cyanobacteria (27.8% OTUs) were dominant.